Evaluating the membrane fouling formation and chemical cleaning strategy in forward osmosis membrane filtration treating domestic sewage. Issue 12 (19th October 2018) - Ab Hamid, Nur Hafizah; Ye, Liu; Wang, David K.; Smart, Simon; Filloux, Emmanuelle; Lebouteiller, Thibault; Zhang, Xiwang
Abstract : Free nitrous acid (FNA) shows strong potential as an effective cleaning reagent in fouling control in a forward osmosis filtration system, with a relatively longer time required. Abstract : As a novel filtration process driven by osmotic pressure, forward osmosis (FO) filtration process offers low fouling propensity and is a potential solution to energy generation and resource recovery from wastewater via direct filtration enriching pollutants into small volume of concentrate. In this study, the characteristics of fouling formation on cellulose triacetate (CTA) FO membranes were investigated using direct filtering of raw domestic wastewater in a FO process. The cleaning efficiency of three environmentally friendly reagents (i) reverse osmosis (RO) water, (ii) ethanol (70 w/w%) and (iii) free nitrous acid (FNA) (35 mg HNO2 –N per L), in fouling control and membrane stability was evaluated through flux and selectivity measurements. From ten successive cleaning cycles, the efficiency of these cleaning reagents in the membrane flux recovery follows the order of ethanol (8.01 ± 0.31 L m −2 h −1 (LMH)) > FNA (5.83 ± 0.36 LMH) > RO water (3.55 ± 0.29 LMH) > control (2.09 ± 0.28 LMH). Although ethanol completely recovered the water flux performance and inactivated the biomass from the fouling layer, it appeared to have compromised the membrane integrity, which was demonstrated by an increased apparent reverse salt flux. After 1 hour of cleaning with ethanol, the apparent reverse salt flux dramatically increased to between 12.58 g m −2 h −1 and 47.21 g m −2 h −1 . The FNA did not show any sign of deteriorating the CTA membrane integrity, however, 94% inactivation of bacteria required 8 hours of exposure time. These results indicate that FNA shows good potential to be used as a cleaning reagent in FO processes for membrane fouling control. Further studies are still needed to improve the efficiency of FNA dosing and required exposure time.